2023
DOI: 10.1111/ijfs.16685
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the bioaccessibility of citrus polyphenols during industrial freezing process

Nurdan Ozdemirli,
Senem Kamiloglu

Abstract: SummaryCitrus fruits can be consumed fresh or they can be subjected to various processes including freezing to extend their shelf life. The aim of the current study was to evaluate the bioaccessibility of polyphenols in samples collected at different stages of the industrial freezing process of oranges and grapefruits. The major polyphenols were identified and quantified using UPLC‐ESI‐MS/MS and HPLC‐PDA, respectively. In addition, spectrophotometric methods were employed to determine the total phenolic and fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…The loss of these glycosylated flavonoids may also be attributed to their cleavage to aglycones [55]. The detrimental effect of industrial freezing on glycosylated flavonoids has been documented in previous studies, particularly in oranges, wherein narirutin and rutin levels exhibited a significant reduction after industrial freezing (53-65%) (p < 0.05) [18]. The alterations in flavonoid bioaccessibility in organic Butternut squash throughout various stages of the industrial freezing process are outlined in Table 2.…”
Section: Flavonoidsmentioning
confidence: 77%
See 1 more Smart Citation
“…The loss of these glycosylated flavonoids may also be attributed to their cleavage to aglycones [55]. The detrimental effect of industrial freezing on glycosylated flavonoids has been documented in previous studies, particularly in oranges, wherein narirutin and rutin levels exhibited a significant reduction after industrial freezing (53-65%) (p < 0.05) [18]. The alterations in flavonoid bioaccessibility in organic Butternut squash throughout various stages of the industrial freezing process are outlined in Table 2.…”
Section: Flavonoidsmentioning
confidence: 77%
“…These models offer the benefits of being quick, cost-effective, and free from ethical constraints encountered in human studies [15]. Despite the presence of a limited number of papers examining the changes in the bioaccessibility of bioactive compounds as a result of industrial freezing process [16][17][18], to the best of our knowledge no previous study investigated the changes in the bioaccessibility of carotenoids and polyphenols in organic Butternut squash at different stages of the industrial freezing process. Similarly, although there are several studies in the literature that have applied in vitro gastrointestinal digestion models directly to fruit and vegetable wastes [19][20][21][22], this study stands out as the first to investigate the bioaccessibility of carotenoids and polyphenols from squash wastes.…”
Section: Introductionmentioning
confidence: 99%
“…To increase the percentage of dry ice particles obtained, the carbon dioxide cylinder is inverted. Open the valve of the carbon dioxide cylinder, the liquid carbon dioxide flows out of the cylinder, flows through the pressure reducing valve, the temperature drops sharply and reaches the gas-solid boundary, forming dry ice particles, which can be explained by the Joule Thomson expansion effect, and then flows through the flow regulating valve and flowmeter to the dry ice nozzle, which is connected to the inlet of the quick freezing tank, and the dry ice particles enter the quick freezing tank through the nozzle, sublimation takes away the heat of the mango [12] , causing it to freeze. The carbon dioxide gas generated is discharged from the outlet of the quick freezing tank.…”
Section: Dry Ice Spraying Systemmentioning
confidence: 99%
“…For example, Ozdemirli and Kamiloglu reported that the industrial freezing process improved the polyphenols’ bioaccessibility of grapefruit while negatively affecting those of oranges. 11 Concerning heat treatments, although many authors pointed out that heat improves polyphenols’ bioaccessibility due to the disruption of the cell wall and breaking polyphenol–polysaccharide complexes, 12 others like Moreno-Ortega et al , who have studied the influence of heat treatment in garlic and onion, reported that treatment had a negative impact on the polyphenols’ bioaccessibility compared to fresh bulbs. 6,13…”
Section: Introductionmentioning
confidence: 99%